Transparency and liveness in visual programming environments for novices - Tanimoto, Steven L. (2015 IEEE Blocks and Beyond Workshop (Blocks and Beyond), 2015)
Blocks-based programming environments offer an alternative program representation to textual source code that simplifies the considerations of syntax for novices. This position paper raises the question of whether additional affordances related to transparency of data, transparency of semantics, and liveness of execution can be consistently added to these environments to obtain some significant advantages for these novice programmers.